CHARACTERISTICS OF CAUSES, CLINICAL, AND SUBCLINICAL SYMPTOMS IN ADULT PATIENTS WITH IRON DEFICIENCY ANEMIA AT DONG THAP GENERAL HOSPITAL - Thanh Tòng, Trần; Quốc Duy, Phạm; Phước Bình, Dương; Tấn Phát, Võ (Journal of Health and Aging, 2026)
Iron deficiency anemia (IDA) constitutes a significant global health issue. Recent studies indicate that 8-15% of iron deficiency anemia cases are attributable to gastrointestinal malignancies. This study presents a series of cases to elucidate the clinical and paraclinical characteristics, etiologies of iron deficiency anemia (IDA), and to assess the correlation among certain variables in patients. The study results included 119 patients aged 16 years and older diagnosed with iron deficiency anemia (IDA) from June 2024 to May 2025 indicated a median age of 60 ± 17.4 years, with 59.7% being female. Prevalent symptoms of anemia include dizziness, vertigo (96.6%), and pallor of the skin and mucous membranes (82.4%). The majority of individuals with severe anemia (87.4%) exhibited inadequate bone marrow response (RPI = 0.3 ± 0.1). The median ferritin level was 10.3 ± 7.5 ng/mL, exhibiting a strong correlation with red blood cell shape (MCV, MCH, MCHC) and transferrin levels. The primary cause was chronic iron deficiency, with 9.2% attributed to gastrointestinal neoplasms, predominantly affecting men at a rate of 72.7%. Studies indicate that TMTS is a prevalent condition, particularly among women and the elderly. It is crucial to screen for the etiology of iron deficiency, particularly gastrointestinal neoplasms, in elderly males.